STUDY ON PROHIBITION OF DISCRIMINATION AGAINST HUMAN RIGHTS OF THIRD GENDER: WITH SPECIAL REFERENCE OF TPPR ACT BY INDIAN PARLIAMENT IN 2019 - Soni, Sonali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Transgender is an encompassing phrase that refers to individuals whose gender identification diverges from the sex assigned to them at birth. People frequently use "trans" as an abbreviation for transgender. This study aims to analyse the prohibition and discrimination against human rights of third gender with the special references of TPPR act. This research examines the problems faced by transgender in India, International and National initiatives regarding rights of third gender and discussed the legislative and legal perspective of third gender in India through TPPR, NALSA act and case studies. This research concludes that India seeks gender justice, with transgender people seeking legislative reform to empower them. Political and public interest organisations should integrate gender sensitivity into legislative reforms, and governments should promote the "third gender" and transgender acceptance. They should also engage with NGOs to enrol transgender kids in elementary and secondary schools.